A homeostatic model of IκB metabolism to control constitutive NF‐κB activity - Ellen L O'Dea; Derren Barken; Raechel Q Peralta; Kim T Tran; Shannon L Werner; Jeffrey D Kearns; Andre Levchenko; Alexander Hoffmann (Molecular Systems Biology)
Abstract Cellular signal transduction pathways are usually studied following administration of an external stimulus. However, disease‐associated aberrant activity of the pathway is often due to misregulation of the equilibrium state. The transcription factor NF‐κB is typically described as being held inactive in the cytoplasm by binding its inhibitor, IκB, until an external stimulus triggers IκB degradation through an IκB kinase‐dependent degradation pathway. Combining genetic, biochemical, and computational tools, we investigate steady‐state regulation of the NF‐κB signaling module and its impact on stimulus responsiveness. We present newly measured in vivo degradation rate constants for NF‐κB‐bound and ‐unbound IκB proteins that are critical for accurate computational predictions of steady‐state IκB protein levels and basal NF‐κB activity. Simulations reveal a homeostatic NF‐κB signaling module in which differential degradation rates of free and bound pools of IκB represent a novel cross‐regulation mechanism that imparts functional robustness to the signaling module.